The Correlation between Spiritual Intelligence and Self Efficacy to the Patient with Type 2 DM in The Workplace area of Primary Health Center III of North Denpasar - Wika Arpandyani, I Gusti Ayu; Manangkot, Meril Valentine; Kamayani, Made Oka Ari (Journal of A Sustainable Global South, 2022)
Diabetes Mellitus (DM) is a elevated blood glucose levels due to decreased insulin secretion. Increased cases of DM if not untreated will cause complications for patients. These complications can be reduced by sustainable management for changing the patient behavior. The lack of DM’s management was determined by various factors such as spiritual intelligence and self efficacy. The aim of this study was to know the correlation between spiritual intelligence and self efficacy in patients of type 2 DM in the Primary Health Center III of North Denpasar. This study was a non-experimental study with correlational design. The sample consisted of 43 persons selected by consecutive sampling technique. The data were collected by questionnaire SISRI and DMSES to know the score of spiritual intelligence and self efficacy. Data were analyzed using Pearson Product Moment test. The results of this study indicated there is the positive correlation between spiritual intelligence and self efficacy with sufficient correlation, p value 0,019 (p ? 0,05). Spiritual intelligence was giving 12,6 % influence on self efficacy, the rest was influenced by the other factor. It was expected that patients can apply spiritual intelligence and self efficacy in everyday life so that it could prevent the occurrence of DM complications.